Penerapan Program Mentoring Dan Coaching Untuk Penguatan Kapasitas Kepemimpinan Pada UMKM Di Desa Adat Panglipuran Bangli Bali - Arum Aji Fitriani; Alya Audina; Gymnastiar Trisatya; Prieya Widy Astuti; Tania Wulandari; Heri Usodo (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2025)
Panglipuran Traditional Village in Bangli, Bali, is a cultural tourism destination with significant economic potential through the development of Micro, Small, and Medium Enterprises (MSMEs). However, MSME actors face challenges in terms of limited leadership capacity to manage their businesses sustainably. This community engagement program aims to strengthen the leadership capacity of MSME actors through the implementation of mentoring and coaching programs. The methods included an initial needs assessment, mentoring sessions facilitated by experienced practitioners, and individual coaching to enhance leadership skills, decision-making, and business management. The results showed improvements in participants’ understanding of adaptive leadership concepts, communication skills, and team management. Furthermore, participants were able to formulate simple business strategies aligned with local potential. Thus, mentoring and coaching programs proved to contribute significantly to strengthening the leadership capacity of MSMEs in Panglipuran Traditional Village, serving as a foundation for business sustainability and increasing competitiveness in culture-based tourism.